Custom v. standardized risk models - Zura Kakushadze; Jim Kyung-Soo Liew (Risks, 2015)
We discuss when and why custom multi-factor risk models are warranted and give source code for computing some risk factors. Pension/mutual funds do not require customization but standardization. However, using standardized risk models in quant trading with much shorter holding horizons is suboptimal: (1) longer horizon risk factors (value, growth, etc.) increase noise trades and trading costs; (2) arbitrary risk factors can neutralize alpha; (3) "standardized" industries are artificial and insufficiently granular; (4) normalization of style risk factors is lost for the trading universe; (5) diversifying risk models lowers P&L correlations, reduces turnover and market impact, and increases capacity. We discuss various aspects of custom risk model building.
Keywords: 330; risk model; multi-factor; risk factor; short horizon; quant trading; style; industry; specific risk; factor risk; portfolio optimization